Selected factors related to physical activity among persons with heart failure in a university-affiliated hospital, Bangkok, Thailand - Saiwutthikul, Sittigorn; Siripitayakunkit, Apinya; Duangbubpha, Sumolchat (Belitung Nursing Journal, 2021)
Background: Heart failure is a complex clinical syndrome that disturbs physical and psychological health and the quality of life of persons with heart failure and their families. Physical activity is one of the essential self-care in persons with heart failure, which can decrease the exacerbation of the heart failure symptoms, increase activity tolerance, ability to accomplish daily activities, and improve quality of life. Objectives: This research aimed to determine the physical activity level among persons with heart failure and explore the relationship between physical activity and its related factors based on the self-and family management framework, including motivation, functional ability, family support, and perceived quality of patient-provider relationships. Methods: A correlational cross-sectional study was conducted with a total of 70 participants who visited the Multidisciplinary Heart Failure Clinic of a university-affiliated hospital, Bangkok, Thailand, from December 2020 to May 2021. Participants were asked to complete five questionnaires that explored their physical activity and its related factors. Data were analyzed and reported using descriptive statistics and correlation coefficient, and the p-value of .05 was considered to be statistically significant. Results: The results showed most participants (78.50%) had a high physical activity level, and the other participants (21.50%) had a moderate physical activity level. Regarding the relationship between physical activity and its related factors, a total physical activity had a significant positive correlation with a functional ability (rs = .309, p < .05), and family support (r = .210, p < .05). While the physical activity had a positively non-significant correlation with motivation (r = .050, p > .05), and a negatively non-significant correlation with perceived quality of patient-provider relationships (r = -.049, p > .05). Conclusion: The research can be used to gain more understanding of physical activity among persons with heart failure. Nurses play an accountable role in promoting and providing appropriate interventions to constantly maintain and enhance physical activity as secondary prevention in persons with heart failure. Additionally, measuring physical activity using an objective measurement with the self-report should be considered for the favorable outcome.